Marketing Strategy Analysis in Increasing Muslim Clothing Sales (Case Study of Erni Umi Syayuzi Store in Perbaungan Serdang Bedagai) - Mira Nur Aisah; Armayani, Reni Ria; Nurbaiti (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
The purpose of this research is to find out what marketing strategies are implemented by the Umi Erni Syayuzi Muslim Clothing Store. Descriptive analysis is one of the data analysis strategies used in this research project using a qualitative method approach. Information was collected through documents and direct conversations with Erni Umisyayuzi, the shop owner. The author conducted research at the Erni Umisyayuzi Muslim Clothing Shop which is located in Perbaungan District, Serdang Bedagai Regency, North Sumatra, Jln. Sena Direction Clear Citakan, Kampung Tempel. Based on the research results, the Syar'i Erni Umisyayuzi Muslim Clothing Store uses sponsored advertising, social media marketing, and collaboration patterns to market its goods online and offline. Apart from that, the Erni Umisyayuzi Muslim Clothing Store also implements a marketing strategy by creating a marketing mix consisting of four components, namely product, price, location and promotion, which adheres to Islamic economic marketing principles.